FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA SISTEM INFORMASI AKUNTANSI PADA DEALER PT ASTRA INTERNATIONAL Tbk. DI SURABAYA - Ivana, Dione; Wehartaty, Tineke (Widya Mandala Surabaya Catholic University, 2016)
At this time, Accounting Information Systems is needed by the company to face a tighter business competition. Presentation of an relevance, accurate and timeliness information is one of the key success to the company. A good Accounting Information Systems per-formance becomes very important to produce financial information and accounting management information that required in decision-making activity. The aim of this study was to find factors that can affect the performance of Accounting Information Systems. The object in this research is the employees of finance and operational department also other related departments which using Accounting Infor-mation Systems in Dealer PT Astra International Surabaya. Sample collection method used in this study is the convenience sampling method. Data in this study were analyzed using multiple linear regression technique analysis. The results of this study showed that personal technical Systems Information skills, top management support, the formalization of Systems Information Development and user education and training programs have significant positive effect on the performance of Accounting Information System. User participation in the system development process not positive influencing the performance of Accounting Information Systems.